Characteristics and importance of protected karst springs in the southern mountainous region of Albania - Jashiku, Ermira (Acta carsologica, 2025)
Karst formations in Albania cover an area of 6750 km2, which represents 24% of the country's territory. The country has 110 karst springs with discharges exceeding 100 litters per second. Among these, Bistrica springs stands out as the largest, with an average discharge of 18.4 cubic meters per second. This study focuses on the Southern Mountain Region of Albania, known for its important karst water resources. In this region, 12 karst springs are protected due to their essential natural, scientific, educational, aesthetic and economic value. The objective of this research is to perform a geoinformatics analysis and evaluation of these protected karst resources. To achieve this, we collected extensive literature on protected springs, as well as reach data about the protected springs of the study area and analysed them using ArcGIS 10.1 software to generate geoinformation about these resources. This geoinformation includes a wide range of geographic and geologic-hydrogeological data. We aim to improve the understanding and promotion of protected karst resources in the Southern Mountain Region of Albania.
Keywords: Albania; Albanija; geografske informacije; geoinformation; geološki spomenik; geomonument; karst springs; kraški izviri